What Influences a Career: A Personal Reflection. Issue 1 (4th October 2022) - Fairfield, Donald H.
Abstract: A scientific career is shaped by factors such as an individual's personality, background, and even uncontrollable exterior factors. Understanding oneself is crucial to one's development as is also the element of luck and being in the right place at the right time. The authors career spanning the development of magnetospheric physics illustrates these points and is described here. Plain Language Summary: The author uses his long career in magnetospheric physics to illustrate some factors that may determine one's professional development. Key Points: One's personality plays a role in determining one's career Luck may influence one's career Consulting other knowledgeable people is important